Prognostic values of VEGF and IL-8 in malignant pleural effusion in patients with lung cancer. (20th May 2013) - Cheng, Daye; Kong, Hong; Li, Yunhui
Abstract: Objective : The aim of this study was to evaluate the prognostic value of VEGF and IL-8 in pleural effusion in patients with lung cancer. Materials and method : Commercially available ELISA was used to determine VEGF and IL-8 levels. Results : The level of VEGF showed significant correlations with lymph node metastasis and distant metastasis. But, IL-8 was only correlated with lymph node metastasis. Univariate and multivariate analysis revealed elevated VEGF level was an independent predictor of shorter OS and DFS. Conclusion : VEGF could be an important component that contributes to pleural effusion formation, and an important prognostic factor for lung cancer.